HUBUNGAN DURASI MENONTON TIKTOK DENGAN PRODUKTIVITAS TUGAS KULIAH MAHASISWA PGSD UNIVERSITAS RIAU - Ninyda Destri Nur Rizkya; Jesi Alexander Alim; Zakiah Ulya (STKIP Subang, 2025)
The rapid development of information technology has brought significant changes in the patterns of social interaction, including among students. One of the most popular social media today is TikTok, which not only functions as entertainment but also as a means of communication, information, and learning. However, the high intensity of TikTok use can affect students' academic productivity, especially in terms of time management and completing college assignments. This study aims to determine the relationship between TikTok viewing duration and the productivity of college assignments of students in the Elementary School Teacher Education Study Program (PGSD) FKIP University of Riau. The research method used is quantitative with a correlational approach. Data were collected through a Likert-scale-based questionnaire distributed to 48 PGSD students from the classes of 2023, 2024, and 2025. The results of the descriptive analysis showed that the majority of respondents had a high intensity of TikTok use, with 60% of respondents in the score categories 4 and 5. The results of the Spearman correlation test showed a value of r = 0.523 with a significance of p < 0.001, which means there is a positive and significant relationship between TikTok viewing duration and student college assignment productivity. This study emphasizes the importance of time management and wise use of social media so that TikTok use can support, rather than hinder, students' academic productivity.